Benefits of Erinacines from Different Cultivate Formulas on Cognitive Deficits and Anxiety-Like Behaviour in Mice with Trimethyltin-Induced Toxicity - Yaovapa Aramsirirujiwet; Teerachart Leepasert; Danita Piamariya; Wachiryah Thong-asa (Tropical Life Sciences Research, 2023)
We investigated the neurological effects of the varied erinacine composition of different mycelia cultures in mice with trimethyltin (TMT)-induced neurodegeneration. Forty male ICR mice were randomly divided into five groups of Sham-veh, TMT-veh, TMT-EME, TMT-EMR and TMT-EME/R. The TMT groups received 2.6 mg/kg one-time intraperitoneal injections of TMT. Oral dosages of 200 mg/kg erinacine combination from each Hericium erinaceus mycelia (EM) cultivated formula (100% eucalyptus wood [E], 100% rubber wood [R], or 40% eucalyptus wood/60% rubber wood [E/R]) were given for 2 weeks. Spatial learning, memory, flexibility, and anxious behaviour were evaluated alongside brain tissues’ oxidative status and histological analyses. Erinacine composition from EME/R exhibited significant positive effects on spatial learning, memory, flexibility, and anxiety (p < 0.05). These findings emerged concurrently with the significant mitigation of hippocampal lipid peroxidation, CA1 hippocampal, cortical neuron, and corpus callosum white matter degeneration (p < 0.05). These neurological benefits were associated with the EME/R composition of erinacine A, C, D, G, H, I, K and R. The best neuroprotective effect against TMT-induced neurodegeneration in mice is offered by the EME/R erinacine composition according to its anti-lipid peroxidation, its nurturing effect on neuronal and white matter, and mitigation of behavioral deficits.